Current Updates on Choanal Atresia - Kwong, Kelvin M. (Frontiers in Pediatrics, 2015)
Choanal atresia (CA) is a relatively uncommon but well-recognized condition characterized by the anatomical closure of the posterior choanae in the nasal cavity. Since the original description back in the early 18th century, there have been controversies regarding its exact pathogenesis, the optimal surgical approach and the use of adjunct treatments such as post-surgical stenting and anti-neoplastic agents, despite of abundant literature available. The emergence and development of new technologies play a significant role in the management of this condition. This review provides a comprehensive clinical update on CA and identifies areas for future study based on the existing available literature.